On the unusual magnetic response of cryomilled BiFeO3 polycrystals. (3rd October 2018) - Dias, G. S.; Volnistem, E. A.; Leonardo, J. M. P.; Silva, D. M.; Cótica, L. F.; Santos, I. A.; Garcia, D.
Abstract: In the present work the influence of milling process below 173 K (cryomilling) on the nanostructuration of BiFeO3 powders, synthesized by fast-firing thermal treatment allied to high-energy ball milling, is evaluated as function of milling time as well as balls size/mass ratio. The influence of the cryomilling process on the structural and magnetic properties of BiFeO3 powders is investigated and the key role of the crystallite size on the magnetic response is evidenced. The results show a strong nonlinear magnetic response, which is governed by the crystallite size while induced strain does not play an important role.